Interacting with the enemy: indirect effects of personality on conspecific aggression in crickets. (28th March 2016) - Santostefano, Francesca; Wilson, Alastair J.; Araya-Ajoy, Yimen G.; Dingemanse, Niels J.
Lay Summary: Opponents beat you up more if you are an adventurous individual. In male field crickets, individuals that are more active, explorative, and aggressive, also make their conspecifics more aggressive in response. Personalities of social partners do matter in aggressive contests and are thus a source of indirect effects on behavior. Abstract: In animal contests, individuals respond plastically to the phenotypes of the opponents that they confront. These "opponent"—or "indirect"—effects are often repeatable, for example, certain opponents consistently elicit more or less aggressiveness in others. "Personality" (repeatable among-individual variation in behavior) has been proposed as an important source of indirect effects. Here, we repeatedly assayed aggressiveness of wild-caught adult male field crickets Gryllus campestris in staged dyadic fights, measuring aggressiveness of both contestants. Measurements of their personality in nonsocial contexts (activity and exploration behavior) enabled us to ask whether personality caused indirect effects on aggressiveness. Activity, exploration, and aggressiveness were positively associated into a behavioral syndrome eliciting aggressiveness in conspecifics, providing direct evidence for the role of personality in causing indirect effects. Our findings imply that a multivariate view of phenotypes that includes indirect effects greatly improves our ability to understand the ecology and evolution of behavior.